(3YbO GddBdi aj GdbQGAGJ GdSHY GdYhGdis - (3CHh MjGf eMeO Hf jhSa Hf Ydj GdCfOdSj,J (B745 (3g` s ((3GdeOQSI GdUGdMjI s)
(3ChdgG (B:s
(3HMeOc jG Gddg jSJaJM GdedC hSejJg YbO GddBdi hEfg ZOkG ddbQGAGJ GdYhGdi eaUdkG afGgjc YbOkG ef LhGgQ bO ZOG Ydi dHg GdbGQFjf GdESJYGPI hYhP HdaX ddbQBf ebOekG CYhP Ydi GSe Gddg s
(3BNQgG (B:s
(3hNeSI CHjGJ hYTQjf HYOgG Shi NWHI ZQGA HGgQI GdNdG NJeJ HMeO Gddg EP cfJ HGOjkG Hg adQHi GdMeO BNQkG ced YbO GddBdi ai GdbQGAGJ GdSHY GdYhGdi s
(3GdfSNI HgG MhGTs
(3bUjOIs
(3YdjgG NW GHf MjGf HbQGAI GdcGJH dgG Ydjg hCLGRJg EjGg HgG s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs